Postoperative Skin Injuries Identified as Pressure Sores: A Prospective Study - YAMAZAKI, Mariko; NAMIKI, Akiyoshi; YAMAMOTO, Naoya; KIKUCHI, Taeko; SAITOH, Tomoko; HARADA, Yuzo (THE JOURNAL OF JAPAN SOCIETY FOR CLINICAL ANESTHESIA, 2002)
This study was designed to determine the cause of postoperative skin injuries. Three hundred and eighty-four surgical patients were investigated prospectively. Burn-like redness, blisters or ulcers over the sacrum, buttocks or heel developed on the first or second postoperative day in 6 patients. In 337 cases, we observed and recorded the state of the sacrum and buttocks at 3 time points: immediately before the induction of anesthesia, immediately after the end of operation, and on the morning of the first postoperative day. Observation records demonstrated that the lesions developed were pressure sores and not burn injuries, because the skin was observed to be intact when the operation was completed. Skin redness appeared during operation in 59 out of 337 cases, and after operation in 18 cases. All 6 patients who had pressure sores were not included in 59 cases, but 5 patients were in 18 cases. These results indicate that the development of pressure sores might be linked with poor postoperative management rather than intraoperative management.